2008
DOI: 10.1097/pai.0b013e318168598b
|View full text |Cite
|
Sign up to set email alerts
|

p16, Cyclin D1, Ki-67, and AMACR as Markers for Dysplasia in Barrett Esophagus

Abstract: Barrett esophagus (BE) is an established precursor of esophageal adenocarcinoma (AdenoCa). One hundred and one cases of BE diagnosed by esophageal biopsy and resections were examined morphologically for dysplasia. These were categorized as BE without dysplasia (n=25), indefinite for dysplasia (IND, n=17), low-grade dysplasia (LGD, n=18), high-grade dysplasia (HGD, n=15), and AdenoCa (n=26). Immunostaining for p16 (INK4A/CDKN2A), Cyclin D1 (CCND1), Ki-67, and alpha-methylacyl-CoA racemase (AMACR) was employed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 38 publications
4
20
0
1
Order By: Relevance
“…That study also found AMACR staining in 21% of samples that were originally diagnosed as indefinite for dysplasia. These findings were supported by the results of a study from Scheil-Bertram et al 19 However, a recent study by Shi et al 20 showed AMACR expression at the rates of 12% in Barrett's esophagus without dysplasia, 47% in indefinite for dysplasia, 44% in low-grade dysplasia, 93% in highgrade dysplasia, and 96% in adenocarcinoma, suggesting that AMACR has lower specificity for distinguishing between Barrett's esophagus with and without dysplasia. The strength of AMACR is that the test is a simple qualitative assessment of positive cells.…”
Section: Discussionsupporting
confidence: 79%
“…That study also found AMACR staining in 21% of samples that were originally diagnosed as indefinite for dysplasia. These findings were supported by the results of a study from Scheil-Bertram et al 19 However, a recent study by Shi et al 20 showed AMACR expression at the rates of 12% in Barrett's esophagus without dysplasia, 47% in indefinite for dysplasia, 44% in low-grade dysplasia, 93% in highgrade dysplasia, and 96% in adenocarcinoma, suggesting that AMACR has lower specificity for distinguishing between Barrett's esophagus with and without dysplasia. The strength of AMACR is that the test is a simple qualitative assessment of positive cells.…”
Section: Discussionsupporting
confidence: 79%
“…Approaches chosen have included morphometry, cell adhesion molecule expression, DNA ploidy analysis, loss of heterozygosity at the chromosomal level, p53 mutations and immunohistochemical overexpression, proliferative activity (through immunohistochemical staining of the Ki-67 antigen), p16 anomalies (including promoter methylation, mutations, and loss of heterozygosity), activation of the Wnt pathway (through adenomatous polyposis coli mutations, β-catenin mutations, or one of the other players in Wnt signaling), analysis of patterns of promoter methylation, and more [10][11][12][13][14][15][16]. Although a voluminous literature exists on this subject, as yet, the only clinically used biomarker with a high predictive value is the presence of HGD [10].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to cyclin D1, expression of p16 protein results in cell-cycle arrest in G 1 phase as it has been shown to inhibit cyclin-dependent kinase-induced phosphorylation of retinoblastoma protein. Early genomic abnormalities during EAC development significantly affect p16 protein expression, which can be determined using immunostaining and implemented as a potential biomarker (95). Further large-scale trials are required to confirm cell-cycle abnormalities during EAC development to implement them as a biomarker.…”
Section: Cell Cycle-related Abnormalitiesmentioning
confidence: 99%